HUBUNGAN MOTIVASI DAN KEBIASAAN SISWA DENGAN MINAT SISWA MENGGUNAKAN JURNAL DIGITAL 7 KEBIASAAN ANAK INDONESIA HEBAT BERDASARKAN TECHNOLOGY ACCEPTANCE MODEL (TAM) DI SEKOLAH DASAR (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Technology-based learning requires teachers and students to utilize available technology and adapt it to students’ needs. The launch of the 7 Habits of Great Indonesian Children (KAIH) movement aims to instill positive habits in children from an early age so that they grow into healthy, intelligent, and well-characterized individuals. This study aims to investigate students’ perceptions of the use of the 7 KAIH digital journal in recording daily reflections, based on the Technology Acceptance Model (TAM) by incorporating external variables, namely motivation and habits. The 7 KAIH digital journal, as an innovative and interactive medium, stimulates students’ motivation and habits in forming positive daily behaviors. However, there has been no detailed research examining the use of the 7 KAIH digital journal in elementary schools based on the TAM framework. This quantitative study employs a survey design and a technology acceptance model approach to measure students’ behavioral intentions to use the 7 KAIH digital journal. Data were collected through questionnaires administered to 96 student respondents. The data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The results of hypothesis testing indicate that, in general, students show an interest in using the 7 KAIH digital journal to record reflections on positive habits. Most elementary school students agree that the 7 KAIH digital journal is easy to use and effective in supporting learning.